Review of the genus Silusa Erichson (Coleoptera: Staphylinidae: Aleocharinae) from Japan, with notes on species described from India - Hashizume, Takuto; Maruyama, Munetoshi (Zootaxa, 2026)
The genus Silusa Erichson, 1837 in Japan is revised based on the examination of type material and additional specimens. Four species are recognized as valid members of the genus, excluding species with highly doubtful generic assignment: Silusa (Silusa) biimpressa Bernhauer, 1907 = Silusa chinensis Pace, 1998, syn. nov., Silusa (Silusa) lanuginosa Sharp, 1888, Silusa immutata sp. nov., and Silusa variabilis sp. nov. Both male and female genital structures of the Japanese species are redescribed in detail, allowing reliable identification for the first time. To clarify the status of South Asian taxa, four species described from India by Cameron (1939) as Silusa, are here illustrated and briefly diagnosed with additional descriptions: Silusa (Silusa) infuscata Cameron, 1939, Silusa indica Cameron, 1939, Coenonica distincta (Cameron, 1939), comb. nov. = Coenonica arcusifera Pace, 1998, syn. nov., and “Silusa” nigra Cameron, 1939 (transferred to Oxypodini Thomson). This study resolves long-standing taxonomic confusion in the Japanese Silusa species and provides an updated diagnostic framework for East and South Asian species of the genus.